Exploring the Cross-Linguistic Contribution of Spanish and English Academic Language Skills to English Text Comprehension for Middle-Grade Dual Language Learners. (January 2020) - Phillips Galloway, Emily; Uccelli, Paola; Aguilar, Gladys; Barr, Christopher D.
In this study, we examine the unique and shared contributions of Spanish and English core academic language skills (CALS) to English reading comprehension in a population of Spanish-English dual language learners in Grades 4 and 5 (n = 165). We focus on cross-disciplinary CALS, operationalized as sets of high-utility lexical, syntactic and discourse resources prevalent in school texts. This study finds that Spanish and English CALS are positively and significantly related, and, further, that both sets of skills exert a unique positive influence on English reading comprehension. Aligned with an interpretation of linguistic interdependence between Spanish and English academic language skills, results document their cross-linguistic contribution to reading comprehension for students enrolled in educational programs that foster literacy and content learning regularly in two languages.